A case study of themes of selected food parks in Quezon City in relation to experiential design - Gabbuat, Jasmine D.; Florendo, Raquel B. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
Food park craze started in 2015 but was suddenly declined after two years in the food industry. With this, the study determined the themes of the selected food parks in Quezon City in relation to experiential design. It aimed to know if the existing themes of the food park create memorable experiences for their customers. Convenience sampling was used to choose the food parks located within Quezon City. While the fifteen respondents, who visited food parks several times, were chosen through purposive sampling. Two weeks were spent on data collection. Tools used were ocular observation, photo documentation, survey questionnaires, and focus group discussions. The study showed that in the selected food parks, they were not able to relate and simulate their customers with their existing themes. Colors, styles, patterns and accessories were used to support the theme. However, the theme was not used as an experiential design, but as a visual aesthetic only to attract customers. Thus, the theme did not create any emotional connection with its customers to make them visit the food park often. According to Gilmore and Pine (1998), the designed experience should not only be functional, but also create an emotional connection through engaging, compelling, and consistent context. However, the selected food parks were not able to apply themes properly. The researcher recommend that longer period of the study should be conducted. In addition, food park or restaurant owners are recommended to consult an interior designer or experiential designer when providing new and memorable dining experiences to their customers.
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Food service -- Philippines -- Quezon City; Themed environments -- Design -- Philippines -- Quezon City; Interior decoration -- Philippines -- Quezon City